Docking Studies and Evaluation of Antimicrobial Activity of Chroman Carboxamide Derivatives - Rawat, Pinki; Verma, Saurabh Manaswita; Kumar, Piyush (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: Based on our previous work, a series of chroman derivatives, which were first used as antiepileptic agents, are evaluated for their antimicrobial potency. Materials and Methods: The present study involves docking studies, synthesis and evaluation of in vitro antimicrobial activity against seven bacterial strains and two fungal strains.The activity was tested by agar well dilution and serial tube dilution methods. Results: The majority of the compounds displayed good to excellent antimicrobial activity. The MIC values of the compounds ranged between 25-100 μg/ml against gram-positive bacteria. However, in the case of gram-negative bacteria, the MIC of compounds ranged between 12.5-100 μg/ml. Compounds 4a and 4b displayed the highest antifungal activity (MIC 25 μg/ml) compared with the antifungal drug, fluconazole. Conclusion: The compounds showed high potency against gram-negative bacteria as compared to the gram-positive bacteria. These findings indicate that it might be a starting point for the development of novel and more potent antimicrobial agents in the future.
Keywords: Antimicrobial agents; Chroman derivatives; Turbidity; Zone of Inhibition; MIC